2014
DOI: 10.1371/journal.pone.0107523
|View full text |Cite
|
Sign up to set email alerts
|

Protein Retention Assessment of Four Levels of Poultry By-Product Substitution of Fishmeal in Rainbow Trout (Oncorhynchus mykiss) Diets Using Stable Isotopes of Nitrogen (δ15N) as Natural Tracers

Abstract: This is second part from an experiment where the nitrogen retention of poultry by-product meal (PBM) compared to fishmeal (FM) was evaluated using traditional indices. Here a quantitative method using stable isotope ratios of nitrogen (δ15N values) as natural tracers of nitrogen incorporation into fish biomass is assessed. Juvenile rainbow trout (Oncorhynchus mykiss) were fed for 80 days on isotopically distinct diets in which 0, 33, 66 and 100% of FM as main protein source was replaced by PBM. The diets were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…Using similar diet formulations as to those used in this study to evaluate performance in juvenile rainbow trout (Badillo et al . ) found no differences in protein retention among dietary treatments (0 PBM to 100 PBM), and showed that rainbow trout could be adequately cultured with total fishmeal replacement by PBM. However, Parés‐Sierra, Durazo, Ponce, Badillo, Correa‐Reyes and Viana () in a parallel study reported that trout fed from 0 to 100 PBM found no differences in growth and performance, whereas significant differences were observed in muscle fatty acid profile among treatments, a profile that was reverted by feeding the control diet (0 PBM) at the end of the trial for only 28 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using similar diet formulations as to those used in this study to evaluate performance in juvenile rainbow trout (Badillo et al . ) found no differences in protein retention among dietary treatments (0 PBM to 100 PBM), and showed that rainbow trout could be adequately cultured with total fishmeal replacement by PBM. However, Parés‐Sierra, Durazo, Ponce, Badillo, Correa‐Reyes and Viana () in a parallel study reported that trout fed from 0 to 100 PBM found no differences in growth and performance, whereas significant differences were observed in muscle fatty acid profile among treatments, a profile that was reverted by feeding the control diet (0 PBM) at the end of the trial for only 28 days.…”
Section: Discussionmentioning
confidence: 99%
“…Recently in our lab, we were able to evaluate the protein retention in the rainbow trout (Oncorhynchus mykiss) using nitrogen (d 15 N) stable isotopes, showing that poultry by-product meal (PBM) was better retained than fishmeal (Badillo, Herzka & Viana 2014). Technological developments in the production process have significantly improved the quality standards of PBM and other rendered meals (Sealey, Hardy, Barrows, Pan & Stone 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies in our lab used stable isotopes of nitrogen and carbon to estimate the retention level of amino acids from different protein sources, instead of measuring feed ingestion and digestibility [6,7]. The results provided insights into the utilization of protein sources; however, the role of each amino acid in the intermediate metabolism is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In aquaculture practice, replacement of dietary fishmeal with alternative cheap protein sources is one of the sought-after research issue that has gained significant momentum in the last couple of decades. Both PBM and BSF have all the ideal properties to be used as a substitute for FM (Rimoldi et al, 2018;Zhou et al, 2018 Manuscript to be reviewed the effect of dietary PBM and BSF on the growth performance of aquatic species but yet no research reported the impact on gut microbial structure and cytokine gene expression patterns of commercially important species including crayfish (Badillo, Herzka & Viana, 2014;Gajardo et al, 2017;Zhou et al, 2018). Therefore, the information obtained from this study on the effects of PBM and BSF supplemented diets on gut microbiota and intestine tissue genes will add novel findings that will have a vital contribution to our existing knowledge.…”
Section: Discussionmentioning
confidence: 99%